Die stil stem van die vroue in die vroeë sendingwerk van “der Kaapsche Kerk” in Njassaland (1896–1906)Deel II: Die Afrika-sendingkonteks - Murray, Isabelle (Stellenbosch Theological Journal, 2017)
The quiet voice of the women in the early missionary work of the Cape Church in Nyasaland (1896–1906)Part II: The Africa mission-context Although by 1910 half of the staff of the ‘Kaapsche Kerk’ in Nyasaland was female, their stories have scarcely been told. In this second of two articles, the focus is on giving a voice to some of these early female missionaries by sharing their experiences of the African mission context. As primary source the newly retrieved diaries of Reverend Andrew George Murray, though written from a male perspective, offer an interesting depiction of the role and contribution of Tillie Murray, his wife, and other female co-workers. The second main source is the letters of Bessie Vlok (née Horne), who lived and worked with her husband Eerwaarde TCB Vlok for six months at Livlezi until the untimely death of their firstborn, and only a few days later, herself. Also included as primary sources, are a number of handwritten letters and ‘witnesses’ composed by various female missionaries. These offer earnest reflections on their confrontations, challenges and experiences: Andrew George Murray went to Nyassaland in April 1901; Tillie Theron arrived in June 1902; Bessie joined her husband, TCB Vlok, in Nyassaland in 1885 and died in 1896.